SZOK – jako kategoria w dyskusji o przemocy wobec dzieci - Małgorzata Turczyk (Problemy Wczesnej Edukacji)
SHOCK, as a recurring category that has been present for many years in the discourse on the right of the child/human to freedom from all forms of violence, becomes the focal point around which the considerations of this article are focused. The inspiration for the use of the shock category in education was the process of studying Anton Siemionowicz Makarenko’s Pedagogical Poemate and the analysis of the educational system he created along practical directives for parenting and its pedagogical implications. In the text, a fundamental question is raised about how Makarenko used SHOCK as a tool in the educational process? The text presents an analysis of the SHOCK category based on the behavior of violence against a child and analyzes their pedagogical implications.